Distribution of nanoflagellates in five water masses of the East China Sea in autumn and winter. (February 2016) - Lin, Shiquan; Huang, Lingfeng; Zhu, Zhisheng; Xiong, Yuan; Lu, Jiachang
Abstract: The variations of abundance, biomass and trophic structure of nanoflagellates (NF) among five typical water masses in the East China Sea were investigated in autumn (November 19–December 23, 2006) and winter (February 22–March 11, 2007). It was found that water mass had a significant impact on the distribution of NF. Either in autumn or in winter, the highest abundance and biomass of NF were recorded in the East China Sea Shelf Mixing Water (ECSSMW), and the lowest in the Kuroshio Subsurface Water (KSSW). While in the East China Sea Coastal Water (ECSCW), the abundance and biomass of both heterotrophic nanoflagellates (HNF) and pigmented phototrophic nanoflagellates (PNF) were only slightly higher than that in Taiwan Strait Water (TSW) and Kuroshio Surface Water (KSW). In respect to the seasonal variation, the abundance and biomass of NF in TSW declined in winter, while in other 4 water masses, they showed an increasing trend from autumn to winter, mainly due to the decrease (in TSW) or increase (in ECSCW, ECSSMW, KSW and KSSW) of HNF. The distribution pattern of abundance- or biomass-based PNF/HNF ratio was found to be correlated to the nutrient level of the water mass. Results of Pearson correlation analysis and principle component analysis indicated that PNF was mainly constrained by nutrient supply, and HNF was controlled by food availability in the East China Sea.